Career Satisfaction, Commitment, and Well-being Among Taiwanese Pediatricians - Der-Fang Chen; Tsuen-Chiuan Tsai; Sio-Meng Lei (Elsevier, 2013)
Currently, the pediatrician shortage in Taiwan has raised concerns about pediatricians' workloads and wellbeing. This study aimed to understand in-hospital pediatricians' perceptions toward career satisfaction and their wellbeing. Methods: A questionnaire exploring pediatricians' life management, commitment to work, and work satisfaction was distributed to all the pediatricians (including attending physicians and residents) in 79 certified training institutions in Taiwan. After expert validation and pilot testing, 17 items with a five-point rating scale were developed to reflect the pediatricians' perceptions. There were 287 responses in total, including 180 attending physicians and 107 residents. Factor analysis was used to explore the construct structure underlying the 17 items. Results: None of the 17 items had a "positive" mean score (≥4/5). Using factor analyses, five factors were extracted: commitment to medical career, self-care, benefit, work environment, and job satisfaction, which accounted for 66.97% of the variance. The factor with the lowest scores was self-care, followed by benefit. The mean score of factors ranged from 2.91 ± 0.17 to 1.64 ± 0.1, all considered "negative." Only 33.6% indicated satisfaction with their jobs. Only 60% of the pediatricians liked their medical career and work environment. The reliability alphas of the five factors ranged from 0.85 to 0.60. Conclusion: Currently, Taiwanese pediatricians are not satisfied with their jobs, having low commitment, poor self-care, and little wellbeing. This study provides a possible explanation for why young physicians leave the pediatric sector, and it also reveals the consequences of physician shortage in Taiwan.